Optimizing the Electrical Interface for Large-Scale Color-Center Quantum Processors - Luc Enthoven; Masoud Babaie; Fabio Sebastiano (IEEE Transactions on Quantum Engineering)
Quantum processors based on color centers in diamond are promising candidates for future large-scale quantum computers thanks to their flexible optical interface, (relatively) high operating temperature, and high-fidelity operation. Similar to other quantum computing platforms, the electrical interface required to control and read out such qubits may limit both the performance of the whole system and its scalability. To address this challenge, this work analyzes the requirements of the electrical interface and investigates how to efficiently implement the electronic controller in a scalable architecture comprising a large number of identical unit cells. Among the different discussed functionalities, a specific focus is devoted to the generation of the static and dynamic magnetic fields driving the electron and nuclear spins, because of their major impact on fidelity and scalability. Following the derived requirements, different system architectures, such as a qubit frequency-multiplexing scheme, are considered to identify the most power efficient approach, especially in the presence of inhomogeneity of the qubit Larmor frequency across the processor. As a result, a non-frequency-multiplexed 1- $\,mm^{2}$ unit-cell architecture is proposed as the optimal solution, able to address up to one electron-spin qubit and nine nuclear-spin qubits within a 3-mW average power consumption, thus establishing the baseline for the scalable electrical interface for future large-scale color-center quantum computers.